2020
DOI: 10.3390/molecules25061275
|View full text |Cite
|
Sign up to set email alerts
|

Attraction and Electrophysiological Response to Identified Rectal Gland Volatiles in Bactrocera frauenfeldi (Schiner)

Abstract: Bactrocera frauenfeldi (Schiner) (Diptera: Tephritidae) is a polyphagous fruit fly pest species that is endemic to Papua New Guinea and has become established in several Pacific Islands and Australia. Despite its economic importance for many crops and the key role of chemical-mediated sexual communication in the reproductive biology of tephritid fruit flies, as well as the potential application of pheromones as attractants, there have been no studies investigating the identity or activity of rectal gland secre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 55 publications
1
20
0
Order By: Relevance
“…The major compounds ethyl dodecanoate ( 19 ) and ethyl tetradecanoate ( 25 ) in the present study have also been reported as the major constituents of the rectal glands and headspace volatiles of females in several other Bactrocera [ 8 , 22 , 23 , 26 , 34 ]. The esters of saturated/unsaturated fatty acids and several acids are female specific and have also been reported in other Bactrocera species but in different proportions in each species [ 8 , 22 , 23 , 24 , 26 , 34 , 35 , 36 ]. Interestingly, ethyl dodecanoate ( 19 ) comprised 39.1% in rectal gland samples but 70.2% in headspace samples.…”
Section: Discussionsupporting
confidence: 73%
“…The major compounds ethyl dodecanoate ( 19 ) and ethyl tetradecanoate ( 25 ) in the present study have also been reported as the major constituents of the rectal glands and headspace volatiles of females in several other Bactrocera [ 8 , 22 , 23 , 26 , 34 ]. The esters of saturated/unsaturated fatty acids and several acids are female specific and have also been reported in other Bactrocera species but in different proportions in each species [ 8 , 22 , 23 , 24 , 26 , 34 , 35 , 36 ]. Interestingly, ethyl dodecanoate ( 19 ) comprised 39.1% in rectal gland samples but 70.2% in headspace samples.…”
Section: Discussionsupporting
confidence: 73%
“…GC-EAD analyses of male pheromone or rectal glands extracts have been performed on several tephritid species, including C. fasciventris, C. anonae and C. rosa [213], C. capitata [220,239], B. oleae [286], A. serpentina [192], A. fraterculus [176,[287][288][289], A. obliqua [241] and A. striata [290]. Additional studies performed GC-EAD analyses on the headspace volatiles of both sexes, in the species R. batava [60], Bactrocera frauenfeldi (Schiner) [291], B. musae [75], and C. capitata [222]. In addition to GC-EAD, gas chromatography-electropalpogram detection (GC-EPD) has begun to be used to test the responses of tephritid maxillary palps to the pheromone emissions [291].…”
Section: Identification Of Electrophysiologically-active Volatilesmentioning
confidence: 99%
“…GC-EAD analyses of male pheromone or rectal glands extracts have been performed on several tephritid species, including C. fasciventris , C. anonae and C. rosa [ 214 ], C. capitata [ 221 , 241 ], B. oleae [ 288 ], A. serpentina [ 193 ] , A. fraterculus [ 177 , 289 , 290 , 291 ], A. obliqua [ 243 ] and A. striata [ 292 ]. Additional studies performed GC-EAD analyses on the headspace volatiles of both sexes, in the species R. batava [ 61 ], Bactrocera frauenfeldi (Schiner) [ 293 ], B. musae [ 76 ] , and C. capitata [ 223 ]. In addition to GC-EAD , gas chromatography-electropalpogram detection (GC-EPD) has begun to be used to test the responses of tephritid maxillary palps to the pheromone emissions [ 293 ].…”
Section: Volatile Pheromonesmentioning
confidence: 99%
“…Additional studies performed GC-EAD analyses on the headspace volatiles of both sexes, in the species R. batava [ 61 ], Bactrocera frauenfeldi (Schiner) [ 293 ], B. musae [ 76 ] , and C. capitata [ 223 ]. In addition to GC-EAD , gas chromatography-electropalpogram detection (GC-EPD) has begun to be used to test the responses of tephritid maxillary palps to the pheromone emissions [ 293 ].…”
Section: Volatile Pheromonesmentioning
confidence: 99%
See 1 more Smart Citation